Occupational risk prevention in hospitals based on the Cultural-Historical Activity Theory - Ferreira, Beatriz Eliseu; Vilela, Rodolfo Andrade de Gouveia; Nascimento, Adelaide; de Almeida, Ildeberto Muniz [UNESP]; Lopes, Manoela Gomes Reis; Braatz, Daniel; Mininel, Vivian Aline (FapUNIFESP (SciELO), 2024)
Hospital managers should target occupational risks and harm prevention since this can contribute to the quality of life at work and patient safety. This article aims to elucidate the activity of prevention of occupational risks and injuries in the hospital setting based on analysis of historical and empirical contradictions of the activity system. An exploratory qualitative study grounded in the Cultural-Historical Activity Theory was conducted at a university hospital in the state of São Paulo. Data were collected between September 2021 and January 2022 via individual semi-structured interviews of 9 professionals from the Occupational Health and Safety services and of five hospital managers, involving 20 hours of field observation and document analysis. Despite the expansion of the object of prevention activity, the other elements of the activity system did not adapt to the new demands, causing incompatibilities and contradictions that compromised the attainment of the expected outcomes. The main response actions observed were centered on complying with regulatory items, such as team composition, medical examinations and others, that contribute little toward promoting occupational health and safety.
Prevenção de riscos e agravos à saúde dos trabalhadores hospitalares à luz da Teoria da Atividade Histórico-Cultural
Keywords: COVID-19; Health management; Hospitals; Occupational health; Occupational health services